Farsighted Stability with Heterogeneous Expectations - Francis Bloch; Anne van den Nouweland (Fondazione Eni Enrico Mattei (FEEM), 2017)
This paper analyzes farsighted stable sets when agents have heterogeneous expectations over the dominance paths. We consider expectation functions satisfying two properties of path-persistence and consistency. We show that farsighted stable sets with heterogeneous expectations always exist and that any singleton farsighted stable set with common expectations is a farsighted stable set with heterogeneous expectations. We characterize singleton farsighted stable sets with heterogeneous expectations in one-to-one matching models and voting models, and show that the relaxation of the hypothesis of common expectations greatly expands the set of states that can be supported as singleton farsighted stable sets.
Keywords: C71; D72; D74; 330; Farsighted Stable Sets; Heterogeneous Expectations; One-to-one Matching; Voting; Effectivity Functions